PERSEPSI MASYARAKAT KOTA JAYAPURA DALAM PELAKSANAAN OTONOMI KHUSUS BIDANG KESEHATAN TAHUN 2019 - Kevyn Wahyu Kelana Hia; Turtiantoro - - (Journal of Politic and Government Studies, 2020)
The special autonomy for Papua is aimed at overcoming the problems of disparities between the Papua region and other regions in Indonesia. With this principle, the Special Autonomy Law expands the space for participation of indigenous Papuans in all fields of development. The law on special autonomy also opens space for improvement for a better future, as well as opens space for improvement in the context of fighting for the improvement of welfare, justice, peace, equality of rights, and to open up the development of identity, dignity, and dignity and dignity as a human. This study aims to assess the perception of the people of Jayapura City towards the implementation of Special Autonomy in the health sector for 2019 and assess the obstacles that occur during the implementation of the special autonomy in the health sector of Jayapura city. This research approach is descriptive quantitative, and data was collected by survey techniques.The conclusions drawn from this study are first, the community has understood the implementation of Special Autonomy, secondly, the public health improvement program has not received a satisfactory response from the community, the third community strongly agrees with the free medical treatment program provided by the government, and the fourth is the obstacles that occur. there is a lack of understanding of the JAMKESPA program.